Ten years of riluzole use in a tertiary ALS clinic. Issue 6 (13th April 2022) - Geronimo, Andrew; Albertson, Richard M.; Noto, James; Simmons, Zachary
Abstract: Introduction/Aims: Riluzole is a glutamate inhibitor approved for the treatment of amyotrophic lateral sclerosis (ALS). There are scant data on factors associated with riluzole initiation and adherence. The goal of this study was to describe the use of riluzole at the Penn State Hershey Medical Center (PSHMC) ALS clinic. Methods: A retrospective medical record review of ALS patients seen at the PSHMC from January 2007 to December 2016. A timeline of riluzole use was established for each patient. Factors contributing to dose changes or discontinuations were recorded. Riluzole adherence was assessed using the proportion of days covered (PDC) calculated by the patient‐reported length of riluzole use divided by total time from prescription to death/censor. Multivariable analysis was performed to evaluate the association of demography and clinical course with adherence. Results: Seven hundred twenty‐three records were screened, with 508 (307 men, 201 women) meeting the criteria for inclusion. The median duration of riluzole use was 435 (range, 0‐3773) days. The median PDC for the group was 64%. Those with higher initial overall function and slower rate of decline were more likely to have a larger PDC. No trends in patients' demographics, riluzole use, and tracheostomy‐free survival were found over time. Discussion: A high rate of riluzole initiation and adherence was found in this sample. The most common reasons for dose modification were related to adverse effects, yet social‐, economic‐, and patient‐related factors were also common. The characteristics of riluzole prescription and use have remained relatively unchanged in a single tertiary ALS center over the past 10 years.